(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Celuk Village in Gianyar Regency, Bali, is known as a centre of silver crafts that is part of the tourism industry and creative economy. However, most MSME actors in this village face obstacles in financial management due to the lack of accounting knowledge and the absence of a structured recording system. This community service activity aims to empower MSME actors through manual accounting information system training to improve understanding and skills in recording and compiling financial statements. The training method used combines lectures and hands-on practice, which was attended by 30 participants in May 2025. The results of the evaluation showed that around 80% of participants experienced an increase in their ability to prepare financial statements, such as income statements and cash books. Mrs Komang’s silver business case study shows the success of the implementation of training in real practice. However, challenges still exist, such as low awareness of the importance of accounting and limited access to technology. Therefore, a more interactive training approach and support from the government and related institutions are needed. This training is expected to increase the sustainability and competitiveness of MSMEs in Celuk Village.